Capital market and economic growth in Malaysia: The role of ṣukūk and other sub-components - Yan-Ling Tan; Roslina Mohamad Shafi (ISRA International Journal of Islamic Finance, 2021)
Purpose - The purpose of this paper is to explore the effects of the capital market on economic growth by considering the role of ṣukūk (Islamic investment certificates) and other capital market sub-components in Malaysia between 1998 and 2018. Design/methodology/approach - The empirical investigation is based on the autoregressive distributed lag (ARDL) cointegration bounds test. Findings - The results reveal the prevalence of a long-run equilibrium relationship between capital market variables and economic growth. As expected, bond market components (ṣukūk and conventional bonds) have a positive, albeit insignificant influence on economic growth. In contrast, in the long-term, stock market development - regardless of the indicator used on economic growth - is shown to have a significant and positive effect. The study suggests that stock market sub-components affect Malaysia's economic growth the most. Research limitations/implications - The primary limitation of this study is that only corporate ṣukūk were considered, while government ṣukūk were excluded from the estimation due to a lack of requisite information, resources and data. Practical implications - A strategic framework should be established, especially in pricing efficiencies. Furthermore, there is a need to create more awareness on the benefits of ṣukūk investment among conventional bond investors, including retail investors. Thus, there will be more players in the ṣukūk market, and this will help to improve market liquidity. Originality/value - Apart from conventional capital market sub-components, this study takes into account ṣukūk as a sub-component in the capital market on economic growth using the ARDL framework. Also, this study particularly concentrates on the world's largest ṣukūk issuer, Malaysia, rather than focusing on other ṣukūk-issuing countries.
Keywords: 330; ARDL; Capital market; Economic growth; Malaysia; Ṣukūk